2006
DOI: 10.1258/rsmsmj.51.3.26
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Social Characteristics of Children with Severe Tooth Decay

Abstract: In this selected group of children with poor dental health, those from deprived families were over-represented and had significantly more decay. Severe dental decay was also associated with underweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 14 publications
5
28
0
7
Order By: Relevance
“…This result were similar to the study done by Olivera et al, 13 Norberg et al, 2 Bahuguna et al, 11 Cameron et at, 14 and Benzian et al 15 This can be attributed to the fact that if a child is a fussy eater and underweight, parents may coerce the child to eat or offer tempting food high in carbohydrates to make sure that the child eats thus increasing risk of dental caries.…”
Section: Discussionsupporting
confidence: 87%
“…This result were similar to the study done by Olivera et al, 13 Norberg et al, 2 Bahuguna et al, 11 Cameron et at, 14 and Benzian et al 15 This can be attributed to the fact that if a child is a fussy eater and underweight, parents may coerce the child to eat or offer tempting food high in carbohydrates to make sure that the child eats thus increasing risk of dental caries.…”
Section: Discussionsupporting
confidence: 87%
“…Some studies report a relationship between caries and poor growth. [1][2][3][4][5][6][7][8][9] Two theories may explain this relationship (Fig 1). The first theory is that the direct impact of extensive untreated caries and associated pain and inflammation on the child' s ability to eat may result in undernutrition and growth impairment.…”
mentioning
confidence: 99%
“…While daily diet has an effect on oral health, oral health can play an important role in nutrition and general health status (11). For example, children with infected teeth and toothache run the risk of malnutrition, and this may be coupled with emaciation and arrested growth in height compared to those with unaffected teeth (12). Moreover, there are common factors such as sugary components, the z Abbreviations: DMFT, decayed missing and filled teeth; WAZ, weight for age z-score; WHZ, weight for height z-score; BAZ, BMI for age z-score.…”
Section: Discussionmentioning
confidence: 99%
“…According to Cameron et al, being underweight in children with established dental decay could be due to the inability of chewing, which in turn can affect their food choice (12). Research performed on the nutritional status of children with severe caries showed that dental caries is a risk factor for malnutrition as it triggers loss of nutrition and BMI for age (BAZ), thereby causing a significant health problem (15).…”
Section: Discussionmentioning
confidence: 99%